2016
DOI: 10.1093/jxb/erw087
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of local xylem embolisms induced by soil drying in intactZea maysleaves

Abstract: HighlightDirect X-ray micro-imaging reveals localized xylem embolism under water stress conditions in the leaves of intact maize, with a specific spatial distribution of embolism in terms of xylem structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
(83 reference statements)
0
20
2
Order By: Relevance
“…In the present study, this technique was used to compare the hydraulic vulnerability of stem, roots and leaves within intact seedlings, which had an age of only few months, while previous studies dealt with either saplings or detached organs of adult trees (e.g. Choat et al ., , ; Cochard et al ., ; Bouche et al ., ; Cuneo et al ., ; Knipfer et al ., , ; Ryu et al ., ; Nardini et al ., ; Nolf et al ., ; Scoffoni et al ., ). Interestingly, the mean vulnerability of seedling stems was lower than that of branches from adult trees of A. pseudoplatanus (Ψ 50 −1.60 and −2.2 MPa from Tissier et al ., and Lens et al ., ; respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, this technique was used to compare the hydraulic vulnerability of stem, roots and leaves within intact seedlings, which had an age of only few months, while previous studies dealt with either saplings or detached organs of adult trees (e.g. Choat et al ., , ; Cochard et al ., ; Bouche et al ., ; Cuneo et al ., ; Knipfer et al ., , ; Ryu et al ., ; Nardini et al ., ; Nolf et al ., ; Scoffoni et al ., ). Interestingly, the mean vulnerability of seedling stems was lower than that of branches from adult trees of A. pseudoplatanus (Ψ 50 −1.60 and −2.2 MPa from Tissier et al ., and Lens et al ., ; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…() suggested that higher rates of PLC in micro‐CT based vulnerability curves might be caused by the exposition of samples to heat and/or X‐ray absorption during sample alignment and scanning. However, in our study, samples were not exposed to irradiation during the initial alignment and the scan time was rather short (90 s) compared with other studies (Cochard et al ., ; Choat et al ., ; Knipfer et al ., ; Ryu et al ., ; Nardini et al ., ; Nolf et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large steps have been made recently towards this goal, with the identification of cavitation in the water‐transporting xylem tissue as a primary cause of plant mortality during drought (Bréda et al ., ; Brodribb & Cochard, ; Barigah et al ., ; Anderegg et al ., ; Adams et al ., ). New techniques that visualize the process of cavitation (the spread and formation of air embolisms in the continuous water column within the xylem that connects leaves with water in the soil) have provided unequivocal evidence of the catastrophic nature of xylem failure during acute water stress (Brodersen et al ., ; Delzon & Cochard, ; Brodribb et al ., ,b; Choat et al ., ; Ryu et al ., ; Torres‐Ruiz et al ., ; Skelton et al ., ). Xylem cavitation is not only linked to plant mortality, but also to slow recovery after drought in forest trees (Brodribb et al ., ; Anderegg et al ., ; Skelton et al ., ), indicating the generality of this process in limiting plant growth, productivity and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Embolism removal can apparently be accomplished by nonmutually exclusive mechanisms (Brodersen et al ., ). Gas bubbles in the xylem conduits of some species can dissolve on their own (Lee & Kim, ; Rolland et al ., ; Ryu et al ., ), a process which is governed by temperature, the surface tension of water, plant water potential (Ψ stem ), conduit diameter, and wall surface properties (e.g. hydrophobicity and wall sculpturing; Konrad & Roth‐Nebelsick, ; Kohonen & Helland, ; Rolland et al ., ).…”
Section: Introductionmentioning
confidence: 99%